Table S5 - Guðbrandsson, Jóhannes; Kapralova, Kalina H.; Sigrídur Franzdóttir; Bergsveinsdóttir, Þóra Margrét; Hafstað, Völundur; Jónsson, Zophonías O.; Snorrason, Sigurður S.; Palsson, Arnar (figshare, 2019)
Genetic polymorphisms studied in the population sample of Arctic charr. Transcript_ID: Name of the transcript from the Trinity assembly Variant: Name of variant. Gene: Short name of gene. Gene_name: Long name of gene. Start: Position of polymorphism within contig. Ref: Base(s) of the reference allele. Alt: Base(s) of the alternative allele. Outg: Base(s) in the salmonid outgroup. Chr_NCBI_id: Sequence identifier for chromosome or scaffold in genome. Chr: Name of chromosome. Chr_position: Position mapped to in chromosome. Effect: Which effect does the mutation have on the gene, 3’- and 5’ UTR indicate mutations in those regions, synonymousdo not change the reading frame but mutations that do so are coded as transitions from one amino acid to another (single letter a.a. code) Marker_ID: Abbreviated ID of each marker. Sequence: The sequence used to design the KASP assay, the polymorphism are marked by e.g. [A/T].